Manuel María Pérez López, y Emilio Martínez Mata (eds.). Revisión de Torres Villarroel. Salamanca : Universidad, 1998. 216 p. (Acta Salmanticensia: Estudios filológicos, 270). - Soons, Alan (El Colegio de México, 2001)
Se reseñó: Revisión de Torres Villarroel.